Cooperative Chirality and Sequential Energy Transfer in a Supramolecular Light‐Harvesting Nanotube. (17th December 2018) - Ji, Lukang; Sang, Yutao; Ouyang, Guanghui; Yang, Dong; Duan, Pengfei; Jiang, Yuqian; Liu, Minghua
Abstract: By constructing a supramolecular light‐harvesting chiral nanotube in the aqueous phase, we demonstrate a cooperative energy and chirality transfer. It was found that a cyanostilbene‐appended glutamate compound (CG) self‐assembled into helical nanotubes exhibiting both supramolecular chirality and circularly polarized luminescence (CPL). When two achiral acceptors, ThT and AO, with different energy bands were co‐assembled with the nanotube, the CG nanotube could transfer its chirality to both of the acceptors. The excitation energy could be transferred to ThT but only be sequentially transferred to AO. During this process, the CPL ascribed to the acceptor could be sequentially amplified. This work provides a new insight into the understanding the cooperative chirality and energy transfer in a chiral supramolecular system, which is similar to the natural light‐harvesting antennas.